Model Predictive Control for Smart Buildings to Provide the Demand Side Flexibility in the Multi-Carrier Energy Context: Current Status, Pros and Cons, Feasibility and Barriers. (February 2019) - Zong, Yi; Su, Wenjing; Wang, Jiawei; Rodek, Jakub Krzysztof; Jiang, Chuhao; Christensen, Morten Herget; You, Shi; Zhou, You; Mu, Shujun
Abstract: In this paper, a state of the art review of model predictive control (MPC) for smart buildings to provide demand side flexibility with the purpose of enhancing a high penetration of renewables into the integrated energy systems is carried, including MPC current development status, pros and cons, implementation feasibility and practice barriers. A two-layer hierarchical MPC-based controller is proposed in a case study for a newly-built multi-family building in Copenhagen. The simulation results show that buildings, as a flexible load to the multi-carrier energy system, whose thermal mass is a heat buffer with a large storage potential, can contribute to the grid ancillary services (load shifting or flexibility), based on the economic incentives that the energy/flexibility market offers to end-users.